SISTEM INFORMASI PEMINJAMAN DAN PENGEMBALIAN ASET BMN POLITEKNIK NEGERI TANAH LAUT - Sofyan, Akhmad; Kurdianto; Wicaksono, Hari; Jirah, Aina; Ariyani, Imelda; Isnania, Nur; Putriana, Dina; Aprianti, Winda; Syafaadi Rizki, Afian (POSITIF : Jurnal Sistem dan Teknologi Informasi, 2025)
The management of State-Owned Assets (SOA) is a critical function within government organizations, with the enhancement of service efficiency for the public as a top priority. However, at Politeknik Negeri Tanah Laut, the asset loan process for SOA is still carried out manually, leading to a waste of time and energy. This study aims to address this issue by developing a web-based Asset Loan and Return Information System. The system is built using the Laravel Framework, with PHP as the programming language and MySQL as the database management system. The main actors in this system include Admins, SOA Staff, and Borrowers. The system is designed to improve the efficiency of SOA asset management. In the system's development, Admins are responsible for managing loan and asset data, while SOA Staff handle inventory management. Borrowers can access features such as viewing inventory, submitting loan requests, and monitoring the status of SOA asset loans. The methods used in this research include needs analysis, and the data utilized covers loan information and SOA asset inventory. The results of this study show that the implementation of a web-based system can enhance the efficiency of SOA asset loans and returns at Politeknik Negeri Tanah Laut, reducing the time and energy required, and providing better transparency in inventory management. Based on UAT results, the system received the highest rating in category B with 50%, followed by category A with 30%, and category C with 20%.